Playing to win how strategy really works - Lafley, A. G. (Alan G.) (Harvard Business Review Press, 2013)
Strategy is not complex. But it is hard. It's hard because it forces people and organizations to make specific choices about their future -- something that doesn't happen in most companies. In this book, two well-known business thinkers get to the heart of strategy -- explaining what it's for, how to think about it, why you need it, and how to get it done.